THE COMPLEX MOBILITIES OF RURAL VERSUS URBAN YOUTH: MOBILITY INTO AND OUT OF THE PARENTAL HOME AND ONE’S COMMUNITY - Looker, E. Dianne (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This paper examines the options facing rural versus urban youth as they negotiate the complex mobilities of moving into adulthood. Specifically, it looks at the links between geographic mobility into and out of one’s home community, and mobility into and out of the parental home. Qualitative and numeric data from a longitudinal survey of 1200 youth provide insight into these transitions. Leaving the parental home is clearly a process rather than an event, and for many it is subjective and ambiguous. More rural youth than urban expected to leave both their parental home and their community, for education and work, and more in fact did leave, by age 19 and 22. This pattern reflects the often limited educational and work options in rural areas. Many youth returned to the parental home for varying lengths of time; again, more rural than urban youth followed this pattern. Urban youth more often have the option of staying close to home to pursue further education or find a job. The parental home serves as an important safety net for youth, especially those who may have been pushed to leave because of limited options nearby. Having the option of returning home gives youth an additional way of dealing with the challenges of their complex mobilities. The results confirm that the pressures on rural youth as they grapple with the mobilities options available to them are quite different than those on their urban counterparts. Thus, rural youth are more often faced with the complexities inherent in the links between social and spatial mobilities.